PRE-SERVICE TEACHERS’ PERCEPTION OF THEIR COMPETENCE AND THEIR READINESS FOR TEACHING PROFESSION - Lou Chien Gita Arista (Language-Edu, 2022)
Indonesian government seriously takes the issue of the teacher education graduates who are considered not to have an established ability to become professional teacher in school, even resulting in disagreement with the implementation of the program. This further calls for a more thorough investigation of the inherent legitimacy of new teachers in Indonesia, as well as their quality. The objective of this study was to reveal pre-service teachers' perceptions of their own competency and readiness to teach. This study employed a survey research design involving 67 undergraduate students of university in Lamongan. The result of this research showed that p value (.258) is greater than ɑ (.05), sugeesting that there was no correlation between pre-service teachers’ perception toward their competence and readiness for teaching profession. Nevertheless, on their perceptions, the pre-service teachers perceived their competence and their readiness were positively in good category and ready for teaching profession. By realizing and considering the aspects for the teaching profession, they feel more confident and ready to face the real environment of teaching as their profession.Keywords: pre-service teachers, perception, competence, readiness